Textbook (Wageningen, 1995)
Physical planning concerns land use, spatial structure and the necessary policy decisions. Physical planning is a process resulting in a spatial plan, such as a plant for urban development or a plan for land use. After realisation of the plan it has to be maintained, wich means that new wishes and insights are incorporated in new versions of the plan so that it remains useful for the relevant inhabitants and users of the land.
Keywords: Economic development projects